Thermal analysis of IRT-T reactor fuel elements; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Naymushin A. G. Artem Georgievich; Chertkov Yu. B. Yuri Borisovich; Lebedev I. I. Ivan Igorevich; Anikin M. N. Mikhail Nikolaevich (Power industry, 2015)
Title screen